Peas in a pod? Comparing the U.S. and Danish mortgage finance systems - Jesper Berg; Morten Bækmand Nielsen; James Vickery (Federal Reserve Bank of New York, 2018)
Like the United States, Denmark relies heavily on capital markets for funding residential mortgages, and the Danish covered bond market bears a number of similarities to U.S. agency securitization. In this paper we describe the key features of the Danish mortgage finance system and compare and contrast it to the U.S. system. We also note characteristics of the Danish model that may be of interest as the United States considers further mortgage finance reform. In particular, the Danish system includes features that mitigate refinancing frictions during periods of falling home prices, and offers borrowers the option to repurchase their mortgage at the market price, mitigating "lock-in" effects. Danish mortgage intermediaries also have high capital ratios relative to their risk exposures, contributing to the stability of the Danish market.
Keywords: G15; G18; G21; G23; G28; 330; mortgage; covered bond; securitization; Denmark; United States